PENINGKATAN KOMPETENSI DESAIN GRAFIS DIGITAL BAGI GURU SMA MELALUI PELATIHAN CANVA DI KOTA DUMAI - Dita Rizki Fitria; Pratiwi, Merina; Syarief, Amiroel Oemara (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
The digital transformation in education encourages teachers to create visual and engaging learning media that align with the characteristics of today’s students. One of the essential skills required is the ability to design digital graphics. Canva, a web-based design platform, offers ease of use for teachers in developing creative teaching materials without the need for advanced technical design skills. This activity aimed to improve the competence of high school teachers in Dumai City in utilizing Canva as a supportive learning tool. The training was conducted over two days and involved teachers from various public and private high schools. The methods used included material presentation, live demonstrations, and independent practice. The results of the activity showed increased enthusiasm and enhanced ability among teachers in creating various design products, such as certificates and presentation templates. This activity demonstrates that Canva-based digital graphic design training can be an effective strategy in enhancing the quality of education and strengthening teachers' capacity in the digital era.